Curiosities at war: the police and prison resistance after Mai '68. (3rd April 2018) - Zurn, Perry
Abstract: It is too easy to say of Mai '68 that the police are incurious while protesters are curious, that administrators are incurious and students are curious. A more honest assessment of these moments, striated as they are with social tensions, would identify at least two modes of enquiry and two sets of questions vying for dominance: the one located on the side of the status quo, the other on the side of change. In what follows, I provide historico-theoretical resources to justify that assessment. I first review Michel Foucault and Jacques Rancière's theories of the police, identifying the incipient role of curiosity in their accounts both of resistance and of power and the police. I then turn to the Prisons Information Group (GIP), where I trace the clear clash between state curiosity as implemented by police and resistant curiosity as practised by GIP activists. Finally, in light of this clash, I explore implications for interpreting Mai '68 and Black Lives Matter as instances of curiosities at war.